The Implementation of the Basic Agrarian Law in Fulfilling the Principle of Justice from the Islamic Legal Perspective - Muthalib, Abdul; Pagar, Pagar; Harahap, Arifuddin Muda (Faculty of Law, Universitas Pekalongan, 2024)
The Basic Agrarian Law (UUPA) is an important legal foundation that regulates the utilization and management of agrarian resources in Indonesia. The principle of justice is one of the main principles sought in the implementation of the UUPA, aiming to create a fair and equitable distribution for all segments of society. This article analyzes how the implementation of the UUPA fulfills this principle of justice from an Islamic legal perspective. Islamic law emphasizes the importance of distributive justice, wise management of resources, and protection of the rights of vulnerable groups. This study uses a literature review method, examining related literature on the UUPA, agrarian law, and the principles of justice in Islamic law. The findings of the study show that there is alignment between the values of justice in the UUPA and the concept of justice in Islamic law, particularly regarding land rights distribution and the management of agrarian resources. However, challenges remain in implementing these principles, such as disparities in access and agrarian conflicts, which require fair resolutions in line with Islamic guidance. The article concludes that achieving substantive justice in agrarian management requires synergy between national law and the principles of justice in Islamic law